Supervisão escolar: expectativas e percepções do supervisor escolar, do coordenador de área e do professor, quanto ao desempenho das funções do supervisor escolar: estudo de caso - Kalo, Leila Juliette (1980)
This study aims to show that the performanc~ of the School Supervisor is beIow the desired professional levels.and aIso that expectations and perceptions such performances vary significantly even among supervisors themselveso ab out the Documental research was underta:~en in order to: establish the needed theoretidâl frame Df reference;folmw the historical gen8sis Df School Supervision;and identify GÍi;·'.'-3cteristic functions Df such supervisiono A case study was completed in Curitiba (the whole M U fi í. (; i P a 1 i t Y ) so as to find out: how the School Superv~sor rloe~ his work; how his performance is perceived both ~y jli.iiL'~;81f and other related professionals (Area Coordinators ano teachers), and what professionals expect from school supervision (in what relates to the li s t-t:; d i n o u r da t a c o 11 e c t i o n t o Dl) o activities Data were collected with Likert-type scales and ona personal data questionnaireo Data were submited to two non-parametric tests (Median and Signs) as well as to a parametric one (t) for reasons discussed in me t h o do 1 o g Y c h a p t e r o D b t ai n e d graphicaIly representedo results were as the well On the bases of theoretical foundations and Df our field study, tmat study expectations and perceptions about the School Supervisor's performance, the need to define a policy for school supervision was concluded and a few recommendations were made.